Studi Pengaruh pH Terhadap Stabilitas Warna dan Kuat Tarik Kain Katun dengan Pewarna Alami Antosianin - Susi Rahayu; Sintya Dewi Lestari; arif Budianto; Alfina Taurida Alaydrus; Halil Akhyar (Universitas Hamzanwadi, 2025)
Lombok has become one of the leading tourist destinations, especially with the development of the Mandalika Special Economic Zone. One of the cultural products that has the potential to be offered to tourists is Lombok traditional weaving. The study aims to analyze the effect of the pH of the dye solution on the characteristics of the dyed fabric. The research method uses a mechanical thermal method to obtain anthocyanin powder extraction, standard staining methods namely mordan, staining, and fixation, as well as characterization using tensilons, Color Analyzer software, Hooloovoo, and Encycolorpedi website. The extraction of anthocyanin compounds from teak leaves (Tectona grandis) was successfully carried out by mechanical thermal method. Color analysis and identified color changes are significantly affected by differences in solution pH. The higher the pH used, the darker the color will be produced and the higher the level of color fading in the fabric. The smallest E value is at pH 6 =5.364 and the largest E value is at pH 14 = 17.145. However, an increase in pH tends to increase the tensile strength of the fabric. However, the optimum tensile strength condition was obtained in a solution of pH 12, which was 17.414 MPa, while at pH 13 and pH 14, the tensile strength of the fabric decreased to 16.071 MPa. Based on the analysis of the influence of pH of dye solution on fabric tensile strength, it was identified that a 6th-order polynomial model (determination coefficient R2 = 0.9479) was identified as accurate enough to model the influence of pH on fabric tensile strength. Therefore, this finding has potential in the textile industry, especially in increasing the economic value of Lombok weaving.